2015
DOI: 10.1155/2015/268471
|View full text |Cite
|
Sign up to set email alerts
|

Effects of GUASHA on Heart Rate Variability in Healthy Male Volunteers under Normal Condition and Weightlifters after Weightlifting Training Sessions

Abstract: Objectives. This paper aims at exploring the effects of GUASHA on heart rate variability between healthy volunteers under normal condition and weightlifters after training sessions. Methods. Ten healthy male volunteers under normal condition and 15 male weightlifters after weightlifting training sessions were recruited into two groups. Electrocardiography was recorded before and immediately after 20-minute GUASHA. HRV was calculated in both the time domain and the frequency domain. Results. Stress index was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Studies have shown that guasha can improve local blood circulation and reduce breast swelling 102 . The main mechanism may be related to the promotion of parasympathetic nerve activity 103 . Animal experiments have shown that Guasha has no effect on the morphology of local tissues and is safe and reliable 104 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that guasha can improve local blood circulation and reduce breast swelling 102 . The main mechanism may be related to the promotion of parasympathetic nerve activity 103 . Animal experiments have shown that Guasha has no effect on the morphology of local tissues and is safe and reliable 104 .…”
Section: Resultsmentioning
confidence: 99%
“…102 The main mechanism may be related to the promotion of parasympathetic nerve activity. 103 Animal experiments have shown that Guasha has no effect on the morphology of local tissues and is safe and reliable. 104 Spermatogenesis is regulated by the testicular microenvironment.…”
Section: Acupuncturementioning
confidence: 99%
“…At the superficial level, the marked ability of this technique to produce a marked increase in blood microcirculation and local metabolism has been demonstrated on multiple occasions [61] and has been estimated to be up to 4 times higher than the pre-treatment perfusion index [62]. These effects go beyond just the circulatory system, but the ability of Gua Sha to produce an effect on the nervous system such as a regulation between sympathetic and parasympathetic nervous system activities has also been studied [63]. Even more astonishing is that the effects of this traditional technique go far beyond its potential for the treatment of external pathologies, being able to be an adjuvant in the management of chronic pathologies that are difficult to treat, such as chronic hepatitis.…”
Section: This Is a Technique In Various Asian Medical Practices Thatmentioning
confidence: 99%
“…Studies showed that Guasha could effectively reduce the immediate blood pressure in patients with mild hypertension, [18] relieve muscle pain, [19] and adjust the heart rate. [20] Guasha can also improve the sleep quality of patients with diabetes, epigastric pain, and menopause. [19,[21][22][23][24][25][26][27][28][29] Nevertheless, whether holographic Guasha can improve insomnia in older adults with hypertension remains unknown.…”
Section: Introductionmentioning
confidence: 99%